Comparison of Measured Energy Expenditure Using Indirect Calorimetry vs Predictive Equations for Liver Transplant Recipients. Issue 4 (25th June 2020) - Lee, Seok Joon; Lee, Hak‐Jae; Jung, Yooun‐Joong; Han, Minkyu; Lee, Sung‐Gyu; Hong, Suk‐Kyung
Abstract: Background: To assess the appropriate energy expenditure requirement for liver transplant (LT) recipients in South Korea, 4 commonly used predictive equations were compared with indirect calorimetry (IC). Methods: A prospective observational study was conducted in the surgical intensive care unit (ICU) of an academic tertiary hospital between December 2017 and September 2018. The study population comprised LT recipients expected to remain in the ICU >48 hours postoperatively. Resting energy expenditure (REE) was measured 48 hours after ICU admission using open‐circuit IC. Theoretical REE was estimated using 4 predictive equations (simple weight‐based equation [25 kcal/kg/day], Harris‐Benedict, Ireton‐Jones [ventilated], and Penn State 1988). Derived and measured REE values were compared using an intraclass correlation coefficient (ICC) and Bland‐Altman plots. Results: Of 50 patients screened, 46 were enrolled, were measured, and completed the study. The Penn State equation showed 65.0% agreement with IC (ICC, 0.65); the simple weight‐based (25 kcal/kg/day), Harris‐Benedict, and Ireton‐Jones equations showed 62.0%, 56.0% and 39.0% agreement, respectively. Bland‐Altman analysis showed that all 4 predictive equations had fixed bias, although the simple weight‐based equation (25 kcal/kg/day) showed the least. Conclusion: Although predicted REE calculated using the Penn State method agreed with the measured REE, all 4 equations showed fixed bias and appeared to be inaccurate for predicting REE in LT recipients. Precise measurement using IC may be necessary when treating LT recipients to avoid underestimating or overestimating their metabolic needs.